Research on the spatial behavior conflict in suburban village communities based on GPS tracking and cognitive mapping - Jie Zheng; Xuefeng Bai; Zhuoran Wu; Shuyue Zhang; Tiantian Zhang; Hao Wang (Journal of Asian Architecture and Building Engineering)
Suburban village tourism is supposed to promote happiness. However, as tourists swarm in, suburban village community spaces tend to become spaces of conflict between diverse groups. To balance development and protection, we need to understand such conflict. Spatial behavior conflict is an important index of the conflict between tourists and residents. This paper is a case study of the Shecun community. It obtains data via GPS tracking and cognitive mapping. By employing the spatial behavior conflict model and space syntax, it analyzes the spatial characteristics of the spatial behavior conflict. And lastly, it explores the paths to sustainable development in suburban villages. According to this empirical research, variations do exist in the spatial behavior conflict in Shecun community, whose spaces can be classified into five types based on their conflict intensity; and there is a positive correlation between the community space’s global accessibility and intensity of spatial behavior conflict.